2009
DOI: 10.1089/acm.2008.0440
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effect of Slow PaceBhastrika Pranayamaon Blood Pressure and Heart Rate

Abstract: Vagal cardiac and pulmonary mechanisms are linked, and improvement in one vagal limb might spill over into the other. Baroreceptor sensitivity can be enhanced significantly by slow breathing (supported by a small reduction in the heart rate observed during slow breathing and by reduction in both systolic and diastolic pressure). Slow pace bhastrika pranayama (respiratory rate 6/min) exercise thus shows a strong tendency to improving the autonomic nervous system through enhanced activation of the parasympatheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
99
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(129 citation statements)
references
References 16 publications
(13 reference statements)
6
99
3
4
Order By: Relevance
“…Studies of the cardiovascular system, the peripheral nervous system, and the central nervous system provide evidence that respiratory patterns can exert a significant and immediate influence on a wide range of bodily functions, including changes in blood pressure and sympathovagal balance. Patterned respiration can regulate blood pressure and heart rate [1], as well as regulate rhythmic centers of the brain that control cardiovascular output [2,3]. While the majority of these findings have demonstrated the impact of respiration on cardiac output and other processes in isolated preparations, little work has focused on respiration's direct influence on membrane potential.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the cardiovascular system, the peripheral nervous system, and the central nervous system provide evidence that respiratory patterns can exert a significant and immediate influence on a wide range of bodily functions, including changes in blood pressure and sympathovagal balance. Patterned respiration can regulate blood pressure and heart rate [1], as well as regulate rhythmic centers of the brain that control cardiovascular output [2,3]. While the majority of these findings have demonstrated the impact of respiration on cardiac output and other processes in isolated preparations, little work has focused on respiration's direct influence on membrane potential.…”
Section: Introductionmentioning
confidence: 99%
“…Though originally designed as a way to quiet the mind, these breathing techniques have also shown health benefits, especially in the area of mind-body illness. [4][5][6][7][8][9][10][11][12][13][14][15][16] Studies have suggested that pranayama practices create a relaxed state by enhancing parasympathetic tone. 11,13,16 Several studies have investigated the efficacy of a multimodality yoga intervention, which includes breathing, postures, and/or meditation, in a population of patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16] Studies have suggested that pranayama practices create a relaxed state by enhancing parasympathetic tone. 11,13,16 Several studies have investigated the efficacy of a multimodality yoga intervention, which includes breathing, postures, and/or meditation, in a population of patients with cancer. [17][18][19][20][21][22][23][24][25][26][27][28][29] However, conclusive results are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In yoga, some problems with stability are associated with hemispheric and autonomic imbalance. From the traditional point of view, in males, spatial performance is better during right side nostril breathing and verbal performance is better during left side nostril breathing [1,[24][25][26]. In the case of females, spatial performance is found better during the left side nostril breathing.…”
Section: Discussionmentioning
confidence: 99%